Notes on the “Lima orchid” Chloraea undulata and its record in the hills of Asia, Cañete, Peru - Lleellish Juscamayta, Miguel (2015)
Chloraea undulata is an orchid endemic to Peru. Originally collected by Antonio Raimondi in XIX century, until first half of the last century it has been regarded as a species characteristic of the hills around Lima. The “Lima orchid” Chloraea undulata is considered to be in decline in the hills of Lima province, especially in the type localities of Cerro Amancaes and Cerro El Agustino where urban growth and expansion has been significant. In this paper its presence in the hills of Asia District, 100 km south of Lima, is documented, and we also analyzed the implications of this finding for the species conservation and their habitat.